2014
DOI: 10.1155/2014/857036
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Experimental Encephalitozoon cuniculi Infection in Immunocompetent and Immunosuppressed Mice in Iraq

Abstract: This study was performed to evaluate pathology of experimental Encephalitozoon cuniculi (Iraqi isolate) infection in normal and immunosuppressed mice. Pathological changes were not seen in negative control mice while secondary bacterial infections were noted in the lungs, kidneys, and heart of mice given dexamethasone. Typical E. cuniculi infection lesions were found in brain, livers, lungs, and kidneys of mice given 107   E. cuniculi spores/mouse orally. These lesions were in the form of nonsuppurative mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Also, these means will be very efficient not only to fight the mosquito sand fly vector of such diseases but also to combat the parasite tanks such as rats and stray dogs who are increasingly responsible for many emerging zoonoses [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, these means will be very efficient not only to fight the mosquito sand fly vector of such diseases but also to combat the parasite tanks such as rats and stray dogs who are increasingly responsible for many emerging zoonoses [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infected rabbits eliminate the spores in urine and feces; thus, infection of the host generally occurs after the ingestion of water or food contaminated with infective spores [ 5 ]. Encephalitozoon cuniculi is considered to be an emergent, zoonotic, and opportunistic pathogen in immunocompetent and immunocompromised individuals [ 6 , 7 ]. The spores infect enterocytes and, perhaps through Peyer's patches or interepithelial lymphocytes, spread to the bloodstream or the lymphatic system, reaching the brain, kidney, liver, and other organs.…”
Section: Introductionmentioning
confidence: 99%
“…bieneusi isolates, which supports the zoonotic transmission of some of its genotypes from animals [37] . Others revealed that animals may represent a major source for spore transmission of opportunistic infection in humans [38] .…”
Section: Discussionmentioning
confidence: 99%